Comparison of ammonia air concentration before and during the spread of COVID-19 in Lombardy (Italy) using ground-based and satellite data. (15th August 2021) - Lovarelli, Daniela; Fugazza, Davide; Costantini, Michele; Conti, Cecilia; Diolaiuti, Guglielmina; Guarino, Marcella
Abstract: Several anthropogenic activities have undergone major changes following the spread of the COVID-19 pandemic, which in turn has had consequences on the environment. The effect on air pollution has been studied in detail in the literature, although some pollutants, such as ammonia (NH3 ), have received comparatively less attention to date. Focusing on the case of Lombardy in Northern Italy, this study aimed to evaluate changes in NH3 atmospheric concentration on a temporal scale (the years from 2013 to 2019 compared to 2020) and on a spatial scale (countryside, city, and mountain areas). For this purpose, ground-based (from public air quality control units scattered throughout the region) and satellite observations (from IASI sensors on board MetOp-A and MetOp-B) were collected and analyzed. For ground-based measurements, a marked spatial variability is observed between the different areas while, as regards the comparison between periods, statistically significant differences were observed only for the countryside areas (+31% in 2020 compared to previous years). The satellite data show similar patterns but do not present statistically significant differences neither between different areas, nor between the two periods. In general, there have been no reduction effects of atmospheric NH3 as a consequence of COVID-19. This calls into question the role of the agricultural sector, which is known to be the largest responsible for NH3 emissions. Even if the direct comparison between the two datasets shows little correlation, their contextual consideration allows making more robust considerations regarding air pollutants. Graphical abstract: Image 1 Highlights: We used ground and satellite data to estimate NH3 concentrations in Lombardy. We analyzed the period before, during and after the COVID-19 lockdown. We divided both datasets in three zones: city, countryside and mountain. NH3 concentrations increased by 31% in countryside areas in 2020. No difference was found between pre- and post-lockdown NH3 from satellite data.